Plan estratégico de desarrollo turístico sostenible de la parroquia Chicaña del cantón Yantzaza, provincia de Zamora Chinchipe. - Galarza Guerrero, Andrés Xavier (2014)
This work provides a strategic planning for sustainable tourism management in the Chicaña parish in Yantzaza canton in Zamora Chinchipe Province, which seeks improve the quality of life of its inhabitants and position to Chicaña as a sustainable tourism destination in the Southern Region of Ecuador in an initial period of three years to a final period of ten years. Firstly this work started with a situational analysis of the parish, in which examined different ambits such as: physical space, social and cultural, ecological and territorial, political and administrative, economical and productive. Then, we identified the tourism potential of the parish analyzing the tourism demand and offer, also we identified the existing tourism problems through a SWOT analysis. Finally, the strategic sustainable tourism development plan was established with a philosophical and strategic formulation, with four objectives to accomplish and seven tourism projects than have to implement in the short, medium and long term.